Assessing the Physical Surface Temperature Patterns in Urban Environment (Case Study: Tehran) - Aliakbar Shamsipour; Ghasem Azizi; Mostafa Karimi Ahmadabad; Masoumeh Moghbel (جغرافیا و پایداری محیط)
Different material’s thermo-physical properties have significant impact on near-surface weather condition which leads to the formation of the urban micro-climates so that, these properties are the main reason for difference between urban and rural air temperatures. To extract different land cover surface temperature patterns such as Asphalt, Soil, Cement and Stone, three OPUS 200/300 Data Loggers with six PT100 sensors were installed in Geophysic Weather Station in University of Tehran and the temperatures of land covers were measured in 10 minute-time intervals during one statistical period (2012-2013). Then, using weather condition data gathered from Geophysic weather Station, land covers surface temperature patterns were divided into six categories including Sunny, Rainy, Snowy, cloudy, windy and a day after rain. Generally, one can conclude that different land covers surface temperature completely obey their thermal properties in sunny, windy and cloudy weather conditions so that, some surfaces such as Asphalt and cement which have less thermal conductivity and high absorbency show the highest surface temperature during the day but only there are some fluctuations in temperature behavior in cloudy and windy conditions which are according to the cloud cover changes or wind speed. While, in rainy and snowy conditions both air and surface temperature have many variations because of cloudiness and precipitation ,and the trend of temperature is not sinusoidal and the main factor is permeability; for example some surfaces such as soil with high permeability shows high temperature.